2019
DOI: 10.30699/fdisj.1.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Determination of the Validity and Reliability of the Persian Version of the Patient-Rated Tennis Elbow Evaluation (PRTEE) Questionnaire in Iranian Tennis Players

Abstract: Background and Objectives: The objective of this study was to evaluate the crosscultural adaptation of the Persian version of the Patient-Rated Tennis Elbow Evaluation (PRTEE) in Iranian tennis players with lateral epicondylitis. Materials and Methods: The original version of the PRTEE questionnaire was translated into the Persian language by two bilingual translators in accordance with the instructions provided by Beaton et al. One hundred and two tennis players (64 males and 38 females) suffering from latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In recent years, the use of validated tools has been growing to evaluate treatment outcomes in clinical trials [4]. Studies have shown that self-reported measurements have more validity and reliability than objective measures [5][6][7]. The most important criterion for measuring treatment outcomes from the patient's point of view is to achieve a preinjury functional level when returning to activity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of validated tools has been growing to evaluate treatment outcomes in clinical trials [4]. Studies have shown that self-reported measurements have more validity and reliability than objective measures [5][6][7]. The most important criterion for measuring treatment outcomes from the patient's point of view is to achieve a preinjury functional level when returning to activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, "r" values of 0 -0.19, 0.20 -0.39, 0.4 -0.49, 0.7 -0.89, and 0.9 -1 showed very poor, poor, moderate, strong, and very strong results, respectively [10].…”
Section: Construct Validitymentioning
confidence: 49%
“…This result was expected, as it was similar to other studies. 11,12,14,16,20 However, it was higher than the original version of the PRTEE 32 (ICC = 0.89) and the French version 15 (ICC = 0.86). This difference in the ICC value could be due to the difference of time interval for the test–retest evaluation in the French version (30 min), and the original version (one week later) in comparison to our study (48 h).…”
Section: Discussionmentioning
confidence: 78%
“…Good psychometric properties of the PRTEE are reported in different languages. 1120 The PRTEE is a 15-item questionnaire with two subscales addressing both pain and function (5 pain items, and 10 function items). Items are scored on a 0 to 10 scale, where 0 is the best possible score in each subscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation